Assessment of radiation dose received by prostate cancer and critical organs in 2D and 3D treatment planning. (September 2016) - Omer, Hiba; Mohamed, Yousra Khairi; Suleiman, Abdelmoneim
Abstract : Introduction: The goal of radiotherapy treatment planning is to design a beam configuration which will deliver a homogeneous dose to the specified planning target volume (PTV), ensuring that normal tissue receives a reasonably low dose and that critical organs receive less than their tolerance doses. Purpose: This study was to compare between 2-dimensional and 3-dimensional techniques for external-beam radiation treatment for prostate cancer. Materials and methods: Dose homogeneity within the target volume and doses to critical organs, OAR were evaluated. CT scans of 30 patients with localized prostate cancer were acquired and transferred to the treatment planning systems (TPS). The target volume and uninvolved structures were contoured on axial CT slices throughout the volume of interest. A comparison of the two treatment techniques was performed using isodose distributions, and dose-volume histograms. Results: The dose distribution in 2D and 3D technique were found the same; however, in 2D technique delivers unnecessary radiation doses to the rectum and bladder. For the rectum it was found that the average (V70, V75 and D95) in 2D technique 35.5%, 32.2%, 34% while for 3D: 8.4%, 0.2%, 12%, respectively. For the bladder it also found the average (V40, V65) in 2D technique 80.8%, 74.9% while for 3D 20.4%, 17%, respectively, also the right and left hip in 2D technique the average V50 were 17%, 20%, while for 3D technique were 4%, 3% respectively; so these indicates that the doses in organ at risk in 3D were within limit while in 2D higher than the allowable limit causing a risk to OAR. Also for the planning target volume the average (V95%, V107%) in 2D technique 90.6%, 5.7% while, for 3D technique 94.9%, 3.8 respectively. Conclusion: 3D conformal radiotherapy was shown to be more effective than 2D conventional radiotherapy in decreasing dose to rectum, bladder and both hip but dose distribution, homogeneity and dose coverage to PTV the same. There was no statistical difference between 2D and 3D radiotherapy in terms of V95% or V107% keeping a minimum of 95% dose coverage for PTV and a maximum dose below 107% as recommended by the ICRU planning guidelines.